Gambaran Self-Disclosure Pada Wanita Dewasa Awal Yang Pernah Diselingkuhi - Agoes Dariyo; Ingrid Hartanto; Sandy Kartasasmita (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2019)
Affair is one of the causes of divorce. Research conducted by Glass and Staeheli (2003) states that men tend to have affair more than women. This matter could arouse negative impact on all aspects of a woman's life as a wife. One of the impacts that is the wife becomes closed to others (Zalafi, 2015). The purpose of this study is to see a picture of self-disclosure in early adult women who have been cheated on. The study was conducted with qualitative methods and data collection was taken by observation and interview method for four subjects. The sampling technique used is criterion sampling. The subjects of this study were women aged 20-40 years, were married, and had been cheated by her husband. The results showed that the four subjects managed to do self-disclosure regarding the problem of affair committed by her husband. However, there is one subject that does not meet one dimension of self-disclosure